ANALISIS WARGA RW 13 MANJAHLEGA KOTA BANDUNG TERHADAP PENGELOLAAN SAMPAH - Zahra Zakkiyah; Muhammad Benito; Muhammad Andi Septiadi; Gallant, Muhammad (Indonesian Journal of Environment and Disaster, 2025)
ANALYSIS OF RESIDENTS OF RW 13 MANJAHLEGA, BANDUNG CITY ON WASTE MANAGEMENT This study aims to analyze the community’s behavior and participation in waste management in RW 13 Manjahlega, Bandung City, using the Theory of Planned Behavior (TPB) as the analytical framework. The research employed a qualitative approach through in-depth interviews, observations, focus group discussions (FGDs), and open-ended questionnaires with ten informants selected using purposive sampling. The findings reveal a significant gap between residents’ awareness of waste management and its practical implementation. Economic constraints, limited infrastructure, and weak social norms were identified as major barriers that hinder consistent waste segregation and recycling practices. The study highlights that strengthening community-based initiatives supported by local government policies, additional waste sorting facilities, and continuous environmental education are essential for improving participation. This research contributes to the development of localized waste management strategies that integrate behavioral insights to promote sustainable urban practices.